Efficacy and safety of platinum chain and gold weight implants for paralytic lagophthalmos: a systematic review (Medical Journal of Indonesia, 2021)
BACKGROUND Surgery has been proposed as a treatment of paralytic lagophthalmos. However, no consensus has been reached on the best treatment. This study was aimed to investigate the efficacy and safety between platinum chain and gold weight implants to treat paralytic lagophthalmos. METHODS This study used all randomized controlled trials or observational studies (prospective or retrospective) using platinum chain and gold weight implants for paralytic lagophthalmos surgery that were published from 1990 to 2020 in the PubMed, Cochrane, and Google Scholar databases. Efficacy was indicated by the reduction of ≥3 in lagophthalmos, and safety was measured based on complications after surgery. RESULTS The efficacy of platinum chain and gold weight implants were 60–100% and 10–93.6%, respectively. The complications of platinum chain implant were 0–2.9% of extrusion and 0–3.3% of migration. However, gold weight implant had 0–13.3% of migration. CONCLUSIONS Both platinum chain and gold weight implants have similar efficacy to treat paralytic lagophthalmos. However, gold weight implant has a higher rate of complication.